DARAHKU, IDENTITASKU: EDUKASI DAN PEMERIKSAAN GOLONGAN DARAH DI KALANGAN REMAJA - SAPUTRA, GUSTIADI; PUSPA, EGITA WINDRIANATAMA; FISABILILLAH, FINA; MALENI, RISTA (LPPM Universitas dr. Soebandi, 2025)
ABO blood type is one of the most important human blood classification systems. A blood type test is one of the tests carried out before receiving a blood transfusion or donating blood. A blood type test is a test that is passed before receiving a blood transfusion or donating blood. The problem faced by partners is the lack of activity programs to conduct blood type checks for school students, and many of these teenagers do not know their blood type so this program aims for teenagers to understand and know their respective blood types. Method This activity was carried out in several stages, namely the preparation stage and the implementation stage (counseling, discussion and examination) of direct blood types on 45 students and 5 teachers at SMK TRISAKTI JAYA Bandar Lampung City in January 2025. The results of this activity obtained the number of students with blood type A of 42%, blood type B of 37%, blood type AB of 3% and blood type O of 18%. The conclusion of this activity is that each student already understands the blood type system and knows the type of blood type of each which is done directly.